2020
DOI: 10.1177/0032321720905130
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Public Opinion about Regional Integration: The Rhetoric of Justification and Party Cues

Abstract: The article investigates how justifications used by politicians to explain their positions on policies of regional integration shape public opinion about these policies. I argue that support for a policy position increases when politicians tailor their justifications to the expectations of their audience, and I suggest that this happens even when party cues offer a less effortful way of forming opinions. I test my theoretical expectations in laboratory experiments with diverse samples, which manipulate party c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Similar patterns have been observed in the USA 294 . Anti-immigration attitudes were shaped by social-communicative processes, including elite rhetoric and partisan cue-taking 337 . All of this parallels polarization trends in other regions, including Europe 338 , the Middle East 11 , and Latin America 11 .…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Similar patterns have been observed in the USA 294 . Anti-immigration attitudes were shaped by social-communicative processes, including elite rhetoric and partisan cue-taking 337 . All of this parallels polarization trends in other regions, including Europe 338 , the Middle East 11 , and Latin America 11 .…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Politicians' messages can also improve the consistency of citizen's values, attitudes and opinions (Levendusky, 2010;Petersen et al, 2010). Such processes have been shown to be relevant for EU-related attitudes as well (Hellström, 2008;Pannico, 2017;Stoeckel & Kuhn, 2018;Vössing, 2020), especially for less knowledgeable citizens and harder issues (Pannico, 2017), even when the political elites are divided (Stoeckel & Kuhn, 2018).…”
Section: Existing Research and Theoretical Expectationsmentioning
confidence: 99%
“…Third, because election periods teem with political information that exceeds the voter's ability to process, the voter's perceptions will pass through an editing process, during which the voter will restrict her attention only to relevant and salient pieces of information, while 'pruning' irrelevant or muddy ones (Lau and Redlawsk, 2006, p.27). Previous research has extensively shown how cue-taking from parties affects voters' perceptions (Vössing, 2020), a process I may extend to forming the substance of party ideologies. Therefore, clear, consistent, and recurrent sig-nals have better chances to influence the voter's perceptions than noisy or occasional signals.…”
Section: The Role Of Party Strategiesmentioning
confidence: 99%